ANALISIS KINERJA SAYAP ORNITHOPTER SEPERTI-BURUNG SEDERHANA - Aris Sandi; Indra Adji Sulistijono; Endah Suryawati Ningrum (Scientific Journal of Mechanical Engineering Kinematika, 2023)
An ornithopter or flapping-wing is a robot that resembles the wings’ mechanics of birds, insects or bats. The application of this type of UAV ranges from photography to the military. This study's main discussion is designing and constructing the ornithopter wing mechanical system with a double-joint wing flapping system. The novelty submitted in this study was the material used to construct the ornithopter wing, namely rod carbon for the skeleton and plastic for the wing. The aim was to discover the aerodynamic performance of the wing and the whole ornithopter. The study results showed that for single wing, the value of CL/CD was high. However, the ornithopter design should be improved to get the thrust force higher than drag force. In addition, the velocity starts to increase stably at throttle 33.3%. Furthermore, for the ornithopter, it was found that the lift force was greater than the down force, so that, theoretically, the robot could fly. The largest lift occurred when the frequency values were 0.88 and 0.97